Synchronization of Coupled Networks with Mixed Delays by Intermittent Control - Kun Yuan; Jinde Cao; Shumin Fei (Journal of Applied Mathematics)
The synchronization of coupled networks with mixed delays is investigated by employing Lyapunov functional method and intermittent control. A sufficient condition is derived to ensure the global synchronization of coupled networks, which is controlled by the designed intermittent controller. Finally, a numerical simulation is constructed to justify the theoretical analysis.